Thinking locally: Environmental reconstruction of Middle and Later Stone Age archaeological sites in Ethiopia, Kenya, and Zambia based on ungulate stable isotopes. Issue 106 (May 2017) - Robinson, Joshua R.
Abstract: Our knowledge of the Pleistocene environments of Africa consists primarily of data at a scale too coarse to capture the full habitat variation important to hominins 'on the ground.' These environments are complex, highly variable, and poorly understood. As such, data from individual sites are a needed addition to our current paleoenvironmental reconstructions. This study offers a site-based approach focusing on stable isotope analyses of fossil faunal tooth enamel from three archaeological sites in tropical Africa. Carbon and oxygen stable isotope data are reported from the sites of Porc Epic, Ethiopia, Lukenya Hill, Kenya, and Kalemba Rockshelter, Zambia. Stable isotope data from tooth enamel are used to measure two environmental variables: (1) aridity based on oxygen isotope composition and (2) dietary reconstructions of fossil ungulates based on the relative proportions of C3 browse and C4 graze in the diet. These data allow for a preliminary assessment of existing models that attempt to explain the behavioral and technological variation characteristic of the transition between the Middle and Later Stone Ages. Results indicate spatial and temporal variation in aridity and phytogeography in tropical Africa during the Pleistocene, suggesting that no single model is likely to provide an explanation for the transition at all sites across Africa.